HUBUNGAN ANTARA ASUPAN NATRIUM, KALIUM, KALSIUM DAN MAGNESIUM DENGAN KEJADIAN HIPERTENSI PADA REMAJA DI SMA NEGERI 10 KOTA SEMARANG - Arini Widhi Adyana; Sri Noor Mintarsih; Ana Yuliah Rahmawati (Poltekkes Kemenkes Semarang, 2016)
Background: Hypertension in adolescents increased morbidity and mortality. Sodium excess in the blood and food causes hypertension. Research conducted Lestari (2010) showed a low potassium intake 2x can risk of suffering from hypertension. Calcium can a role in blood pressure control, regulation and contraction of smooth muscle and blood vessel walls. Magnesium with potassium, calcium, and sodium role in the regulation of blood pressure for cardiovascular prevention. Based on Riskesdas (2013) cases of hypertension in Indonesia in the age group 15-17 years of 5.3%. Objective:To identify theassociated intake of sodium, potassium, calcium and magnesium with hypertension in adolescents in Senior High School 10 Semarang. Methods:The study of public nutrition research community with a case control approach matching sex ratio of 1: 1, each sample of cases and controls were 31 students. Collecting data include measurement of blood pressure, intake of sodium, potassium, calcium and magnesium. To determine the relationship between variables used Mc Nemar testwith ???? = 95%. Results: Univariate analysis found an average blood pressure systole / diastole in the case group is 131.35 / 75.41 mmHg in the control group is 104.03 / 60.87 mmHg. Sodium intake in both groups of 50% in more categories, potassium intake 90% in the poor category, the calcium intake 80% in the poor category, magnesium intake 20% in the poor category. The results of the bivariate analysis there is no relationship between sodium intake (p = 0.092), potassium (p = 1.000), calcium (p = 0.687) and magnesium (p = 0.250) with hypertension Conclusion:The intake of sodium, potassium, calcium and magnesium are not associated with the incidence of hypertension in SMAN 10 Semarang. Advised students reduce high sodium intake, increasing the intake of potassium, calcium and magnesium